2022
DOI: 10.1039/d2cp01125e
|View full text |Cite
|
Sign up to set email alerts
|

Influence of vanillic acid immobilization in Nafion membranes on intramembrane diffusion and structural properties

Abstract: Pulsed field gradient (PFG) NMR in combination with quasielastic neutron scattering (QENS) was used to investigate self-diffusion of water and acetone in Nafion membranes with and without immobilized vanillic acid...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 44 publications
3
11
0
Order By: Relevance
“…This regime is defined by a coincidence of the water attenuation curves and an essentially monoexponential shape of these curves. In complete analogy with our previous data for acetone diffusion in Nafion loaded with water/acetone mixtures 17, 18, it is expected that such third regime occurs for all other DMMP concentrations in the limit of long diffusion times. However, the relatively short proton T 1 NMR relaxation times of water in the measured samples prevented an observation of the third regime for all other DMMP concentrations.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…This regime is defined by a coincidence of the water attenuation curves and an essentially monoexponential shape of these curves. In complete analogy with our previous data for acetone diffusion in Nafion loaded with water/acetone mixtures 17, 18, it is expected that such third regime occurs for all other DMMP concentrations in the limit of long diffusion times. However, the relatively short proton T 1 NMR relaxation times of water in the measured samples prevented an observation of the third regime for all other DMMP concentrations.…”
Section: Resultssupporting
confidence: 85%
“…Our previous PFG NMR studies 17, 18 of water diffusion in Nafion have discussed the observed time dependence of the PFG NMR data for water, which were analogous to those reported in the current work, in the context of water diffusing along water channels that are not fully interconnected in Nafion membrane. The diffusion data were explained by the existence of micrometer‐sized domains inside Nafion in which these channels are interconnected for water to diffuse.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations